Upacara Sapuh Leger Sebagai Aplikasi Ajaran Manusa Yadnya di Lingkungan Padang Griya Kelurahan Padangsambian Denpasar Barat - Ratih, Ida Ayu; Dharma Putra, Anggara Putu; Laksana Utama, Putu Kussa (Widya Duta: Jurnal Ilmiah Ilmu Agama dan Ilmu Sosial Budaya, 2019)
In Hindu, someone who is born to coincide with wuku wayang is a child who falls into the category of "cemer", because it has the same birthday as Bhatara Kala. Bhatara Kala will eat every child who has the same birth day as him, so to avoid the pursuit of Bhatara Kala every child is required to carry out the Sapuh Leger Ceremony. This study aims to address several issues including: (1) The procession of the Sapuh Leger Ceremony, (2) Application of the teachings of Manusa Yadnya, (3) the meaning of symbols in the Sapuh Leger Ceremony in the Padang Griya Environment, Padangsambian Village, West Depasar.This type of research is qualitative, with the determination of informants using the purposive sampling method. As well as collecting data using non-participant observation, structured interviews with recording techniques, recording and shooting, and literature study methods. Data analysis conducted in this study used a descriptive qualitative method.The results of the study showed that the procession of the Sapuh Leger Ceremony in the Padang Griya Environment Padangsambian Village, West Denpasar was carried out from morning to noon, starting from offering offerings to Ida Sang Hyang Widhi as a manifestation of Oton God, licking to cleanse themselves in beji and in the Lord Shiva Buddhist temple. The application of the teachings of Manusa Yadnya in the Sapuh Leger Ceremony lies in the procession of the implementation of the Natab Banten Oton procession. Meaning of symbols in the Sapuh Leger Ceremony is found in the Facilities used in the ceremony and staging of the Sapuh Leger Puppet. So that through each symbol used in the ceremony to form a communication to deliver a message so that children born in wuku wayang always find prosperity in their lives.